1999
DOI: 10.1155/1999/920109
|View full text |Cite
|
Sign up to set email alerts
|

Guidelines for Follow‐Up of Women at High Risk for Inherited Breast Cancer: Consensus Statement from the Biomed 2 Demonstration Programme on Inherited Breast Cancer

Abstract: Protocols for activity aiming at early diagnosis and treatment of inherited breast or breast-ovarian cancer have been reported. Available reports on outcome of such programmes are considered here. It is concluded that the ongoing activities should continue with minor modifications. Direct evidence of a survival benefit from breast and ovarian screening is not yet available. On the basis of expert opinion and preliminary results from intervention programmes indicating good detection rates for early breast cance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(25 citation statements)
references
References 24 publications
(23 reference statements)
2
23
0
Order By: Relevance
“…As such, this confirms the lack of consensus and/or reluctance regarding this procedure observed in previous research among GPs and other health care professionals [4, 15, 16, 17]as well as among women from breast cancer families [18, 19, 20, 21]and from the general population [4]. It also mirrors the careful position of several professional associations of medical specialists in Europe and the US [22, 23, 24]. Still, almost one third of the GPs explicitly endorsed a prophylactic mastectomy as being ‘the best method to prevent breast cancer’.…”
Section: Discussionsupporting
confidence: 84%
“…As such, this confirms the lack of consensus and/or reluctance regarding this procedure observed in previous research among GPs and other health care professionals [4, 15, 16, 17]as well as among women from breast cancer families [18, 19, 20, 21]and from the general population [4]. It also mirrors the careful position of several professional associations of medical specialists in Europe and the US [22, 23, 24]. Still, almost one third of the GPs explicitly endorsed a prophylactic mastectomy as being ‘the best method to prevent breast cancer’.…”
Section: Discussionsupporting
confidence: 84%
“…This corroborates the disagreement and/or reluctance regarding this procedure found in previous studies among general practitioners and other health care professionals [8, 17, 18], as well as among women from breast cancer families [19, 20, 21]and from the general population [22]. As such, it also reflects the prudent position taken by professional associations of medical specialists in Europe and the US concerning preventive options for carriers of a HBC mutation [23, 24]. On the other hand, unambiguous support for prophylactic mastectomy in the prevention of breast cancer was reported by almost one fifth of the sample in our study – which is a somewhat smaller proportion of supportive respondents than was found in a recent study among general practitioners [8].…”
Section: Discussionsupporting
confidence: 85%
“…For breast and ovarian cancer, inclusion was based on the Biomed 2 Demonstration Program. A subject was included in the surveillance program if she had a family history of two or more first-degree relatives with early onset of breast cancer (<50 years of age), and/or multiple cases of breast cancer in the same lineage compatible with dominant inheritance in the family, and/or a combination of early onset breast cancer and ovarian cancer in the family [23]. Inclusion in the HNPCC surveillance program was based on the Amsterdam I criteria.…”
Section: The Gc Protocolmentioning
confidence: 99%